Let's evaluate the given algebraic expressions step by step.
-
For the expression:
\( 18 - 30x \)
Substituting \( x = \frac{1}{3} \):
\( 18 - 30(1/3) \)
Now calculating \( 30(1/3) \):
\( 30 \times \frac{1}{3} = 10 \)
So we have:
\( 18 - 10 \)
\( = 8 \)Therefore, the first blank is 10.
-
For the second expression:
\( 2(9 - 15x) \)
Substituting \( x = \frac{1}{3} \):
\( 2(9 - 15(1/3)) \)
Now calculating \( 15(1/3) \):
\( 15 \times \frac{1}{3} = 5 \)
So we have:
\( 2(9 - 5) \)
\( = 2(4) \)
\( = 8 \)Therefore, the second blank is 4.
Putting it all together, the filled-in blanks are:
18 - 10
2 (9 - 15(1))
2 (9 - 5)
Notice that both expressions simplify to 8, confirming the consistency.